Crossword Puzzle-Based Active Learning to Enhance Engagement and Achievement in Civics Education - Halik, Halik; Wati, Ery; Ariani, Tasya (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
This study investigates the effects of implementing a crossword puzzle-based active learning model in Civics Education (PPKn) at SMA Negeri 2 Indrajaya. Persistent challenges with student engagement and low learning outcomes, often linked to long-standing lecture-based practices, motivated the intervention. Using a classroom action research approach over two cycles, the study involved Grade XI.1 students in collaborative crossword-solving activities designed to reinforce core subject concepts. Results showed that the proportion of students meeting the minimum competency standard increased from 0% at baseline to 60% after the intervention. Classroom observations documented more equitable participation, higher motivation, and improved group collaboration. However, the model did not achieve the targeted mastery threshold of 75%. Several factors—including entrenched passive habits, varying levels of student readiness, and the limited intervention period—contributed to this gap. The findings highlight both the promise and the challenges of adopting active learning strategies in established classroom environments. Sustained teacher support, professional development, and ongoing adaptation will be essential for achieving broader and more durable impacts. Future research should explore long-term outcomes and the effectiveness of active learning models across diverse educational settings.